Axonal protein synthesis: a potential target for pain relief? - Obara, Ilona; Géranton, Sandrine M; Hunt, Stephen P (Current opinion in pharmacology, 2012)
► Nociception can be regulated at the level of local mRNA translation in nociceptors. ► Local mRNA translation can occur in primary afferents under the control of mTOR and ERK pathways. ► mTOR and ERK pathway inhibitors can reduce pain behavior. ► mTOR and ERK pathways may act independently, depending on the type of sensory afferents. Research on the role of axonal protein synthesis in the regulation of nociceptive mechanisms has grown significantly over the past four years. Recent advances include evidence that local translation of mRNA can occur in adult primary afferents under the control of the mammalian target of rapamycin (mTOR) and the extracellular signal-regulated kinase (ERK) signaling pathways. Studies investigating the effect of mTOR and ERK pathway inhibitors in a number of pain models suggest that these signaling pathways may act independently, depending on the type of sensory afferents studied. The evidence that nociception can be regulated at the level of mRNA translation in nociceptors has important implications for the understanding of the mechanisms of nociceptive plasticity and therefore for therapeutic interventions in chronic pain conditions.